Factor VIIa and its potential therapeutic use in bleeding-associated pathologies - Hedner, Ulla (Thrombosis and Haemostasis, 2008)
Recombinant FVIIa (rFVIIa) was developed for treatment of haemophilia patients with inhibitors against FVIII/FIX. The haemostatic efficacy rate of 80–90% including major orthopaedic surgery (dosing of 90–120 µg/kg every other hour [h] for at least the first 24 h) was achieved in these patients. In a home-treatment setting the efficacy rate of haemostasis in mild-moderate bleedings was 92% (average number of 90 µg/kg doses was 2.2). A wide individual variation regarding recovery of rFVIIa (46 ± 12%; median 43%) as well as of clearance rate (36 ± 8 ml/kg/h; median 32 ml/kg/h in adults;children 2–3 times higher) has been observed. Thus children may require higher doses than adults. Accordingly the use of a dose of 270 µg/kg in one single injection was approved in the EU. Recent experience indicates that repeated doses of rFVIIa may decrease the number of bleeds in “target joints”, and thus may be useful as prophylaxis in severe hemophilia with inhibitors. Pharmacological concentrations of rFVIIa have been shown to enhance the thrombin generation on thrombin activated platelets in a cell-based model. By doing so a tight structured fibrin haemostatic plug resistant against premature lysis is formed. rFVIIa has been shown to induce haemostasis not only in haemophilia but also in other situations characterized by an impaired thrombin generation such as platelet defects, dilution coagulopathy developed as a result of trauma and extensive surgery. A special form of profuse bleeding, that may cause extensive problems is postpartum haemorrhage.
Keywords: Factor VIIa; haemophilia therapy; haemostasis; haemophilia A / B; tissue factor / factor VII